2018
DOI: 10.2172/1466530
|View full text |Cite
|
Sign up to set email alerts
|

System Levelized Cost of Energy Analysis for Floating Offshore Vertical-Axis Wind Turbines

Abstract: The levelized cost of energy for an offshore wind plant consisting of floating vertical-axis wind turbines is studied in this report. A 5 MW Darrieus vertical-axis wind turbine rotor is used as the study turbine as this architecture was determined to have the greatest ability to reduce the system cost. The rotor structural design was used with blade manufacturing cost model studies to estimate its cost. A two-bladed, carbon fiber rotor was selected in this analysis since the lower topside mass resulted in a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…38,39 Therefore, inspecting the momentum and turbulence distribution under the wake interaction has been of increasing interest for HAWTs (e.g., previous studies 37,40,41 ), and it would be of similar interest for that of VAWTs, as the wind energy industry is seeing a potential boost of offshore VAWT farms due to their advantages in floating environments. 42,43 Hence, experimental investigation on the wake interaction of VAWTs located upwind and downwind is desirable. This work investigates the wake interactions of VAWTs placed inline and with offset employing stereo-PIV, focusing on whether the wake deflection of VAWT gives more energy to an array configuration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…38,39 Therefore, inspecting the momentum and turbulence distribution under the wake interaction has been of increasing interest for HAWTs (e.g., previous studies 37,40,41 ), and it would be of similar interest for that of VAWTs, as the wind energy industry is seeing a potential boost of offshore VAWT farms due to their advantages in floating environments. 42,43 Hence, experimental investigation on the wake interaction of VAWTs located upwind and downwind is desirable. This work investigates the wake interactions of VAWTs placed inline and with offset employing stereo-PIV, focusing on whether the wake deflection of VAWT gives more energy to an array configuration.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these models are subject either to oversimplified governing equations such as linear superposition or to the ill‐defined superposition of turbulence fields 38,39 . Therefore, inspecting the momentum and turbulence distribution under the wake interaction has been of increasing interest for HAWTs (e.g., previous studies 37,40,41 ), and it would be of similar interest for that of VAWTs, as the wind energy industry is seeing a potential boost of offshore VAWT farms due to their advantages in floating environments 42,43 …”
Section: Introductionmentioning
confidence: 99%
“…The maintenance costs and the total lifetime energy output are dependent on how the system operates and, consequently, depend on the environment and how it is controlled [21,22]. Recent studies have shown that advanced control strategies for offshore wind applications can increase the power extracted from the turbine and minimize the levelized cost [23,24]. Most conventional LCOE estimates have not incorporated detailed dynamic assessments nor the impact of novel control strategies.…”
Section: Introductionmentioning
confidence: 99%
“…the meantime HAWT research gained momentum and it became the industry standard for multi-megawatt scale wind energy conversion systems. Despite these issues, interest in VAWTs have resurfaced especially in offshore deep-water conditions and it has been discovered VAWTs might challenge HAWTs in terms of efficiency and cost-effectiveness (Simão Ferreira (2009); Griffith et al (2018); Ennis and Griffith (2018)).…”
Section: Introductionmentioning
confidence: 99%